PENGARUH LKS BERMUATAN KECERDASAN KOMPREHENSIF DALAM MODEL PROBLEM BASED INSTRUCTION TERHADAP KOMPETENSI FISIKA SISWA KELAS X MAN 2 PADANG - Fauzy Dwi Ardi; Nurhayati Nurhayati; Zulhendri Kamus (PILLAR OF PHYSICS EDUCATION, 2017)
Competences that must achieved by student based on 2013 curriculum are attitude, knowledge and skills. Unfortunately , learning process conducted at school is not totally covered these competence yet. The purpose of the research is to investigate the influence of student worksheets contain of comprehensive intelligence in Problem Based Instruction model towards the physic competence students in class X of MAN 2 Padang on the spiritual attitude, emotional and social attitude, knowledge and skills. The type of this research is Pre Experimental Design with One Shoot Case Study. The population of the research is all of student in class X MIA MAN 2 Padang that registered on the 2016/2017 period. Sampling purposive technique used to get the sample. Sample in this research is class X of MIA 2. Research instrument in the form of a final test for knowledge competence, observation sheets for attitude competence and performance sheet for skill competence. Based on the data analysis, the average value for of spiritual attitude is 78,35, competence of emotional and social is 78,38, competence of skill is 79,26 and competence of knowledge for before and after treatment are 51,39 dan 75,14 respectirely. Competence of knowledge data obtained using t-test berkorelasi which is tcaunt is 13,14 and ttable is 1,70 at 5% significance level of the left side test. In conclution, the student worksheet that contained  comprehensive intelligence can strengthen skills and understanding of students to that physics competence of student can be increased